(untitled) (Encuentros, 2024)
Chilean companies, which make up the Selective Stock Price Index (IPSA), have incorporated the Global Reporting Initiative (GRI) into their annual reports. Some companies have even advanced to the publication of sustainability reports. This study analyzed the annual and/or sustainability reports, between the years 2015 and 2019, of the IPSA companies (as of December 31, 2019). The data obtained was subjected to a mixed qualitative-quantitative analysis to determine the degree of compliance with the GRI G4. The results show that 91.30% of the companies analyzed reach 50% or more of compliance. However, this level of compliance would be strongly influenced by the GRI 101, which provides only general information about the companies.